A Dictionary of Color: A Lexicon of the Language of Color - Ian, Paterson (Thorogood, 2012)
This is an extraordinary book... Everyone involved professionally with colour, in whatever way, will find this book not only intriguing, but of real practical benefit. But above all, there is just the sheer joy of discovery, the sensation of being propelled around a pin-ball machine from one new word or expression to another." Michael Peters, The Identica Partnership